Роль брендбуку у стратегічному формуванні іміджу компанії - Мина, Жанна; Кириченко, Софія (Видавництво Львівської політехніки, 2025)
The thesis explores the role of a brand book in shaping a company's image. It emphasizes how a brand book serves as a strategic tool for ensuring consistent communication, both internally and externally. By defining visual and communicative standards, it helps maintain brand identity, fosters trust with consumers, and supports long-term business goals. The study highlights the significance of a brand book in enhancing internal cohesion, improving marketing efficiency, and facilitating smooth entry into.
Keywords: брендбук; імідж компанії; корпоративна ідентичність; стратегічне управління; візуальна комунікація; комунікаційні стандарти; маркетинг; конкурентоспроможність; корпоративна культура; довіра споживачів